C2.3 Identifying and treating mental health disorders in children and young people with epilepsy: a screening and brief intervention study. (4th October 2017) - Bennett, S; Heyman, I; Varadkar, S; Coughtrey, A; Buszewicz, M; Byford, S; Dore, C; Fonagy, P; Moss-Morris, R; Stephenson, T; Tebbs, S; Walker, E; et al.
Abstract : Background: Children and young people with chronic neurological conditions have significantly higher rates of mental health disorders than those without a chronic health condition, or those with chronic illnesses that do not involve the CNS. Mental health problems can impact on quality of life as well as on the management and medical consequences of the physical illness yet may be relatively easy to treat. However, such mental health disorders often go unrecognised and therefore untreated. The aim of the current study was to establish the feasibility of routine screening and brief telephone intervention for mental health disorders in paediatric neurology clinics. Methods: Parents of children and young people aged 7–18 attending specialist paediatric neurology clinics were asked to complete an online screening questionnaire (the Strengths and Difficulties Questionnaire; SDQ) on a tablet computer in clinic. Those who had symptoms of a mental health disorder were invited to complete a longer online diagnostic questionnaire, the Development and Wellbeing Assessment (DAWBA), at home. Those with impairing symptoms were offered a 10-session guided self-help intervention delivered over the telephone. Standardised measures were completed before, during and after the intervention. Results: The method of identification proved feasible in terms of numbers completing the SDQ (n=406, of which n=232 had significant symptoms of a mental health disorder) and DAWBA (n=124). 76% of those completing the DAWBA met DSM-V diagnostic criteria for a mental health disorder. 40 families took part in the brief intervention and results are promising, with progress made towards families chosen goals and high levels of satisfaction reported by families and clinicians. Conclusions: Children and young people with chronic neurological conditions have high rates of mental health disorders. These disorders can be detected and treated through a simple online diagnostic tool and telephone intervention and this method is acceptable to families.